2019
DOI: 10.48550/arxiv.1904.00137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Feasibility of Sample Average Approximation Solutions

Abstract: When there are infinitely many scenarios, the current studies of two-stage stochastic programming problems rely on the relatively complete recourse assumption. However, such assumption can be unrealistic for many real-world problems. This motivates us to study the cases where the sample average approximation (SAA) solutions are not necessarily feasible. When the problems are convex and the true solutions lie in the interior of the set of feasible solutions, we show the portion of infeasible SAA solutions decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Without this assumption, they demonstrate that in the chained-constrained case the dependence on the parameter m in the convergence rate can be replaced by the number of active constraints in an optimal solution, which, e.g., can be bounded by the number of first-stage variables n 1 . Our results complement those in [11] by conducting a different analysis which does not use the chain-constrained domain assumption nor an assumption that domF lies in the interior of X.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…Without this assumption, they demonstrate that in the chained-constrained case the dependence on the parameter m in the convergence rate can be replaced by the number of active constraints in an optimal solution, which, e.g., can be bounded by the number of first-stage variables n 1 . Our results complement those in [11] by conducting a different analysis which does not use the chain-constrained domain assumption nor an assumption that domF lies in the interior of X.…”
Section: Introductionsupporting
confidence: 67%
“…In this section we assume the set X is finite, such as in the case that all decision variables are integer and bounded. In [5], it has been shown that, in the case when f (x) is real-valued for all x ∈ X, under certain assumptions, the optimal solution set of ( 12) converges exponentially to the optimal solution set of (11). We extend this result to the extended-real-valued objective case.…”
Section: Exact Convergence For Finite Xmentioning
confidence: 79%
See 2 more Smart Citations
“…In [12], the ambiguity sets are taken to be finitely supported Wasserstein metric balls centered at the empirical distributions, and the algorithm is shown to converge asymptotically with stochastic sampling methods. We comment that all of the above variants of DDP algorithms rely on the assumption of relatively complete recourse, while it is indeed possible to have MSCO without such assumption [23].…”
Section: Introductionmentioning
confidence: 99%